PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Sutarno, Indah Wahyuni, Lamidi & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this research is to analyze the effect of compensation, workenvironment and motivation on employee performance, also to analyze the effect ofcompensation and work environment on employee performance with work motivationare moderated variable. This research is included in the scope of human resourcemanagement. The population are employees at PT Waskita Karya (Persero) Tbk totaling78 people so that the whole is used as a sample with total sampling technique. Methodsof data collection used questionnaires and observations. Data analysis techniques usedmultiple linear regression and absolute difference test. The results showed thatcompensation has a significant effect on employee performance. Work environment hasan effect on employee performance. Work motivation has an effect on employeeperformance. Motivation moderates the effect of compensation on employeeperformance and motivation does not moderate the influence of the work environment onperformance of employee.Keywords: teamwork, loyalty, leadership, performance